The Influence of Slot Time and Ground Services on Aeronautical Revenue Through Operational Performance (A Study at PT Angkasa Pura II, Soekarno-Hatta Airport, Tangerang, Banten) - Prasetiyo, Boy Fajar; Aditya Wardhana; Olfebri Olfebri (Dinasti Review, 2025)
This study examines the influence of slot time optimization and ground service quality on airport revenue, with operational performance as an intervening variable. Focusing on Soekarno-Hatta International Airport, this research integrates concepts of operational management and financial sustainability in airport operations. The findings reveal that optimizing slot time significantly enhances operational efficiency, leading to increased aeronautica revenue. Similarly, ground service quality directly improves passenger satisfaction and operational performance, indirectly contributing to higher income. The study highlights the critical role of operational performance as a mediating factor, bridging the gap between resource optimization and financial outcomes. Recommendations for effective airport management strategies include leveraging advanced scheduling systems and enhancing ground service efficiency to maximize aeronautica revenue potential while ensuring service quality and operational sustainability.